Intelligent design algorithm for branching structures based on updated force density method. (1st October 2022) - Zhao, Zhongwei; Yu, Duo; Zhang, Tongrui; Cai, Qi
Abstract: Form-finding analysis has been deeply investigated with the extensive application of branching structures. In addition to the form-finding analysis, another important scientific problem to be resolved is determining the optimal topology of branching structures. The topological study of branching structure is inseparable from form-finding analysis because they are coupled together. An intelligent design algorithm for branching structures based on updated force density method is proposed to deeply investigate the topological form of branching structures. The intelligent design algorithm comprises three sub-algorithms, namely, form-finding algorithm based on force density method, length optimization algorithm based on updated force density method, and topology optimization algorithm. The proposed algorithm can automatically select the effective component to support the load while decreasing the sectional area of the inefficient component. Thus, topology optimization can be achieved by "killing" inefficient components. The component section can be determined in two ways, namely, fully stressed design algorithm and section library selection. The component length can be optimized through the proposed method to maximize the structural stability. The proposed method and research results can lay a foundation for the intelligent design of branching structures. Highlights: An intelligent design algorithm for branching structures is proposed. The buckling capacity can be maximized. The effective members can be automatically selected from the ground structures. The sectional size can be automatically determined.